One Health: governance and regulatory framework for antimicrobial use in Malawi - Amos Lucky Mhone; Dishon M. Muloi; Arshnee Moodley (Science in One Health)
Background: Antimicrobial resistance (AMR) poses a global threat to both human and animal health, associated with widespread use of antimicrobials across sectors. In low- and middle-income countries (LMICs) such as Malawi, weak regulatory frameworks and limited enforcement capacity contribute to inappropriate use of antibiotics. This study examined the governance and regulatory frameworks for antimicrobial use (AMU) in Malawi's agricultural sector, identified regulatory gaps, and offers recommendations to antimicrobial stewardship. Methods: A qualitative approach was used, combining a review of policy and legal documents with semi-structured stakeholder interviews. Relevant policies and laws were sourced from government databases, the Food and Agricultural Organisation of the United Nations' (FAO) FAOLEX and AMR-LEX databases, and other publicly available resources. The FAO's legal assessment methodology was used to evaluate the policy landscape across nine key thematic areas: (1) veterinary medicinal products, (2) animal health and production practices to prevent animal diseases in terrestrial and aquatic animals, (3) feed registration, (4) pesticides, (5) food safety, (6) environment, soil and waste, (7) water quality, (8) plant health, and (9) institutional coordination. Stakeholder interviews with representatives from relevant government ministries and regulatory bodies validated findings from the document review and provided additional insight into governance challenges. A One Health governance mapping exercise was conducted to identify key institutional actors, assess their role in AMR/AMU governance, and evaluate inter-institutional relationships using social network analysis. Results: The analysis identified 522 policies relevant to AMU in agriculture, with most addressing aquatic animal health (11.3 %, n = 59), food safety (10.9 %, n = 57) and animal feed (10.9 %, n = 57). Several critical regulatory gaps were identified, including the absence of a legal definition for “antimicrobials,” a national essential veterinary medicines list, and standardized veterinary treatment guidelines. Additionally, there are no restrictions on the use of critically important antimicrobials for human health in veterinary settings, minimal oversight of antimicrobial-medicated feed, and no established protocols for on-farm antimicrobial disposal. Stakeholder mapping revealed limited knowledge sharing among institutions and a dependence on international donors for AMR/AMU-related activities, raising concerns about the sustainability of current initiatives. Malawi also lacks an integrated AMR and AMU monitoring system, a national prioritised AMR research agenda, and clear targets for reducing AMU in animals. Conclusion: To address these gaps, we recommend that Malawi: (1) establish a comprehensive AMR and AMU monitoring program, (2) update existing regulations to provide clear definitions and classification of veterinary antimicrobials, (3) develop and implement national veterinary treatment guidelines, (4) restrict non-therapeutic AMU, (5) enhance regulatory oversight of medicated feed, (6) strengthen One Health coordination mechanisms, (7) promote stakeholder collaboration, and (8) secure sustainable, nationally driven funding. Implemention of these measures will enhance antimicrobial stewardship, reduce AMU, mitigate the spread of AMR, and support the long-term sustainability of agricultural production in Malawi.